Identifikasi Forensik Berdasarkan Pemeriksaan Primer dan Sekunder Sebagai Penentu Identitas Korban pada Dua Kasus Bencana Massal - Prawestiningtyas, Eriko; Algozi, Agus Mochammad (Jurnal Kedokteran Brawijaya, 2009)
ABSTRACTThe main purposes of identification process in mass disaster is to find the corpses identity in order to give itback to their family by doing some identification methods such as primer identification which must do at thefirst time because they have highly and accurate result as the identifiers. There are many differencesbetween the burned corpses on the the tragedy of the burning of Garuda Airlines and the drowned corpses onthe tragedy of the sinking of Senopati Nusantara ship , many difference characteristic that influence theprocess of forensic identification. In the burned corpses, teeths are still intact and relatives still could beexamined than another primery identifiers. It makes difference priority between one to another cases. So,from the two different cases, we can choose the different primer identifiers as the priority depend on thecondition of the dead bodies related to the accident in order to make the right identity for giving back to therelatives.